Efficient removal of organic compounds from shale gas wastewater by coupled ozonation and moving-bed-biofilm submerged membrane bioreactor. (January 2022) - Liu, Xinyu; Tang, Peng; Liu, Yuanhui; Xie, Wancen; Chen, Chen; Li, Tong; He, Qiping; Bao, Jin; Tiraferri, Alberto; Liu, Baicang
Graphical abstract: Highlights: MBBF-SMBR following ozonation efficiently removes organics from shale gas wastewater. Compared with traditional SMBR, MBBF-SMBR shows higher removal of organics. MBBF-SMBR shows low membrane fouling and suitable resilience during operation. High amount of specific bacteria with biodegradation ability are found in MBBF-SMBR. Enhanced genes about membrane transport and nitrogen metabolism are found in biofilm. Abstract: Shale gas wastewater (SGW) with complex composition and high salinity needs an economical and efficient method of treatment with the main goal to remove organics. In this study, a coupled system consisting of ozonation and moving-bed-biofilm submerged membrane bioreactor (MBBF-SMBR) was comprehensively evaluated for SGW treatment and compared with a similar train comprising ozonation and submerged membrane bioreactor (SMBR) without addition of carriers attaching biofilm. The average removal rates of MBBF-SMBR were 77.8% for dissolved organic carbon (DOC) and 37.0% for total nitrogen (TN), higher than those observed in SMBR, namely, 73.9% for DOC and 18.6% for TN. The final total membrane resistance in SMBR was 40.1% higher than that in MBBF-SMBR. Some genera that specifically contribute to organic removal were identified. Enhanced gene allocation for membrane transport and nitrogen metabolism was found in MBBF-SMBR biofilm, implying that this system has significant industrial application potential for organics removal from SGW.